Assessing the burden of human cysticercosis in Vietnam. Issue 3 (28th December 2012) - Trung, Dung Do; Praet, Nicolas; Cam, Thach Dang Thi; Lam, Binh Vu Thi; Manh, Hung Nguyen; Gabriël, Sarah; Dorny, Pierre
Abstract Objectives To describe the occurrence of cysticercosis in patients living in rural areas of Northern Vietnam presenting clinical signs of neurocysticercosis. Methods Serological antigen detection, reflecting current infection with viable larval stages of Taenia solium, was used to estimate the prevalence of active cysticercosis in this patient population. Results The seroprevalence in epileptic patient population was <10%. However, antigen detection cannot detect dead cysticerci, which may also cause clinical signs. Therefore, the seroprevalence figures shown here may underestimate the role of neurocysticercosis as a causal agent of epilepsy and headaches in this population. Conclusions Human and porcine cysticercosis remain public and veterinary public health problems in Northern Vietnam and probably in other parts of the country.